2005
DOI: 10.1128/iai.73.8.4714-4722.2005
|View full text |Cite
|
Sign up to set email alerts
|

Conditions Influencing the Efficacy of Vaccination with Live Organisms againstLeishmania majorInfection

Abstract: Numerous experimental vaccines have been developed with the goal of generating long-term cell-mediated immunity to the obligate intracellular parasite Leishmania major, yet inoculation with live, wild-type L. major remains the only successful vaccine in humans. We examined the expression of immunity at the site of secondary, low-dose challenge in the ear dermis to determine the kinetics of parasite clearance and the early events associated with the protection conferred by vaccination with live L. major organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 32 publications
4
66
0
1
Order By: Relevance
“…Kaur et al (2008) have reported a strong Th1 response in BALB/c mice by inoculation through subcutaneous route with low dose of live, whole parasite antigen. This has been corroborated by Tabbara et al (2005) and they further reported that vaccination with live parasites through subcutaneous route (s.c.) influences cell types recruited in the secondary site of infection and clears parasites efficiently. On contrary, other workers in the field (Mukhopadhyay et al 1999;Méndez et al 2002) experienced that s.c. route did not work well for the experimental MVL.…”
Section: Discussionsupporting
confidence: 61%
“…Kaur et al (2008) have reported a strong Th1 response in BALB/c mice by inoculation through subcutaneous route with low dose of live, whole parasite antigen. This has been corroborated by Tabbara et al (2005) and they further reported that vaccination with live parasites through subcutaneous route (s.c.) influences cell types recruited in the secondary site of infection and clears parasites efficiently. On contrary, other workers in the field (Mukhopadhyay et al 1999;Méndez et al 2002) experienced that s.c. route did not work well for the experimental MVL.…”
Section: Discussionsupporting
confidence: 61%
“…Our observations demonstrate that the number of parasites that establishes infection must be considered in interpreting the influence of the site of infection, as suggested previously (6). We and others have demonstrated that the relative differences in parasite load or lesion size following inoculation at different sites or with different doses of parasites can change depending on the time of analysis (1,3,7,36,48). For example, while we observed earlier control of parasite numbers in the ear than in the footpad, likely due to the earlier onset of adaptive immunity as shown here, a 10-fold-higher parasite load was maintained in the ear during chronic infection (3).…”
Section: Discussionmentioning
confidence: 59%
“…Vaccination by different routes has also been shown to influence the efficacy of vaccines against parasitic, bacterial, and viral infections, as well as cancer (3,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). In the case of infections initiated in the skin by the bite of an insect vector, such as Yersinia, Plasmodium, Borrelia, and Leishmania infections (29), the use of an intradermal route of infection would appear to be critical, since the initial interaction between these pathogens and the host takes place primarily in the skin under natural conditions (11,15,(30)(31)(32).…”
mentioning
confidence: 99%
“…Depletion or neutralization of CD4 + T cells, CD8 + T cells, IFN-c, IL-12 or NO induces parasite expansion [11,12,22,23]. Conversely, treatment with anti-IL-10R [24][25][26] or anti-CD25 [13] antibodies leads to sterile cure and loss of immunity. Our studies employing the B/6 model (unlike other murine models) reproduce the immunopathology associated with the disease in humans.…”
Section: Discussionmentioning
confidence: 99%
“…T reg cells rapidly accumulate at sites of Lm infection, suppressing the ability of the immune response to completely eliminate the parasite. Furthermore, parasite growth at the site of infection is promoted by T reg cells: Removal of T reg cells early during the infection enhances the capacity of mice to mount effective immune responses and control parasite numbers; transfer of T reg cells to chronically infected mice stimulates local parasite growth and reactivation of disease [13,14].…”
Section: Introductionmentioning
confidence: 99%